(untitled) (International Journal of Innovative Computing, 2021)
Automata theory plays an important role in various areas especially in game design. This paper describes the concept of automata theory in designing one of the most popular classical game which is Hangman. In this study, we focused on a game called Hangaroo, which implemented the same concept as in Hangman game. We studied and discussed the combination of automata and game theory that can be considered in order to design the game. As a result, we found that, automata theory is the fundamental access in designing and developing Games.